2023
DOI: 10.34133/bmef.0004
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in In Vitro and In Vivo Bioreactor-Based Bone Generation for Craniofacial Tissue Engineering

Abstract: Craniofacial reconstruction requires robust bone of specified geometry for the repair to be both functional and aesthetic. While native bone from elsewhere in the body can be harvested, shaped, and implanted within a defect, using either an in vitro or in vivo bioreactors eliminates donor site morbidity while increasing the customizability of the generated tissue. In vitro bioreactors utilize cells harvested from the patient, a scaffold, and a device to increase mass transfer of nutrients, oxygen, and waste, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Bioreactors of the latter type permit the application of a direct mechanical challenge to the tissue, but they generally use cumbersome tools that can significantly hinder oxygen supply to small-sized constructs. Even those that can also enable oxygen transport to tissues are complicated to build to treat small constructs, making it difficult to reliably apply forces to multiple tissue constructs with one compressive head, and are thereby susceptible to rupture and contamination ( Watson and Mikos, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bioreactors of the latter type permit the application of a direct mechanical challenge to the tissue, but they generally use cumbersome tools that can significantly hinder oxygen supply to small-sized constructs. Even those that can also enable oxygen transport to tissues are complicated to build to treat small constructs, making it difficult to reliably apply forces to multiple tissue constructs with one compressive head, and are thereby susceptible to rupture and contamination ( Watson and Mikos, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…In BTE, bioreactors are employed to grow functional tissues from MSCs in controlled in vitro conditions. This process provides a continuous supply of nutrients and the removal of waste products prior to in vivo implantation at bone defect sites [135,136]. Implementing a mathematical model of the process in a CFD simulation involves four key steps: designing the geometries of scaffolds and complimentary bioreactors, selecting the appropriate flow equations, and determining the boundary and initial conditions (Figure 13) [137,138].…”
Section: Parameters Authors Referencementioning
confidence: 99%
“…Experts’ opinions on cell-based bone tissue engineering encompass the following various innovative approaches: (1) Developments in the utilisation of 3D-printed bioresorbable scaffolds, incorporating trace elements of metal like magnesium, which serve to energise cells as scaffold degrades [ 337 , 338 , 339 , 340 , 341 , 342 ], (2) The exploration of piezoelectric 3D scaffolds, leveraging the effects of electromagnetic fields in BTE [ 343 , 344 ], (3) Progress in the development of physiologic bioreactors aimed at efficiently seeding cells and providing mechanical stimulation [ 345 , 346 , 347 , 348 ], (4) The utilisation of induced pluripotent stem cell technologies and investigation into the potential use of exosomes as cell sources [ 349 , 350 , 351 , 352 , 353 ], and (5) The introduction of immune cells, such as neutrophils, to facilitate early vascularisation and auto-regulate vascular growth factors, coupled with surgical techniques [ 100 , 354 ].…”
Section: Future Perspectives On Critical-sized Bone Tissue Engineeringmentioning
confidence: 99%
“…This approach demonstrated remarkable bone regeneration, highlighting its potential for addressing challenges associated with uniformly loading cells in critical-sized bone defects. In recent years, there has been an increasing interest in utilising physiologic bioreactors to facilitate efficient cell seeding and provide mechanical stimulation [ 345 , 346 , 347 , 348 ]. In vivo studies demonstrated the efficacy of neutrophil-mediated bone regeneration, with neutrophil-treated groups showing a higher bone volume fraction in rabbit calvarial defect models [ 100 ].…”
Section: Future Perspectives On Critical-sized Bone Tissue Engineeringmentioning
confidence: 99%